Indigenous fruit trees in the tropics [ domestication, utilization and commercialization - Akinnifesi, Festus K. (CABI Publication in association with the World Agroforestry Centre, 2008)
It has been recognized that an important factor in improving viability of rural livelihoods in developing countries is the promotion of sustainable agriculture. As opposed to relying solely on cash crops, this can be achieved through domestication of various indigenous fruit trees that can be cultivated and owned by smallholder farmers.